The Therapeutic Potential of Nutraceutical in Diabetes Management: A Comprehensive Review - Mohd. Wasiullah; Piyush Yadav; Sushil Yadav; Rishi Prasad Jaiswal (Emerging Trends in Metabolites, 2025)
Diabetes is a long-term and complex condition characterized by high blood sugar levels resulting from inadequate insulin production, ineffective insulin function, or a combination of both. Various nutraceuticals used in clinical settings have shown beneficial impacts on a range of biochemical and clinical markers related to diabetes. In many traditional medical systems, hypoglycemic agents derived from plants are used to treat, manage, and prevent diabetes mellitus. These plant extracts have demonstrated significant clinical benefits in maintaining normal blood glucose and lipid levels. The global use of natural products, herbal remedies, and nutraceuticals in therapeutic applications has been on the rise. Conventional treatment options, including synthetic drugs, often fall short of meeting therapeutic needs across a spectrum of pathological conditions. Nutraceuticals offer a promising therapeutic option for diabetes, potentially causing fewer side effects than synthetic medications. Defined as non-specific biological therapies derived exclusively from organic products, nutraceuticals aim to support health, prevent disease progression, and alleviate symptoms. Nutritional supplements are recognized for their powerful roles in disease prevention, health maintenance, and potentially even disease treatment. This study intends to examine and discuss some of the most utilized nutraceuticals for diabetes prevention.
Keywords: Diabetes mellitus; Insulin; micro-nutrients; nutraceuticals; phytoconstituents